2019
DOI: 10.1007/s00217-019-03263-7
|View full text |Cite
|
Sign up to set email alerts
|

Triticum aestivum ssp. vulgare and ssp. spelta cultivars. 1. Functional evaluation

Abstract: Over recent decades, several types of ancient grain varieties have been reintroduced through organic farming systems. In the past 20 years, there has been a renewed interest in growing spelt, and this species has a market niche in Europe and North America in natural, organic and healthy products. Are there any differences between commercial wheat varieties and spelt? The analysis of the bread-making quality of three bread wheat and two spelt cultivars has found no significant differences between the two types … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 34 publications
1
9
0
1
Order By: Relevance
“…In previous research, quantification of gliadins fractions was done to compare the quantities of gliadin fractions between different wheat species [ 9 , 50 , 108 , 109 ], using only one spelt wheat genotype in each study. Rodríguez-Quijano et al [ 110 ] found considerable differences in the amounts of different gliadin fractions between two spelt varieties, with one of them having more similar values to bread wheat varieties. To the best of our knowledge, until now, no research was conducted to investigate the quantitative variation of gliadin fractions in more spelt genotypes and between different environments.…”
Section: Discussionmentioning
confidence: 99%
“…In previous research, quantification of gliadins fractions was done to compare the quantities of gliadin fractions between different wheat species [ 9 , 50 , 108 , 109 ], using only one spelt wheat genotype in each study. Rodríguez-Quijano et al [ 110 ] found considerable differences in the amounts of different gliadin fractions between two spelt varieties, with one of them having more similar values to bread wheat varieties. To the best of our knowledge, until now, no research was conducted to investigate the quantitative variation of gliadin fractions in more spelt genotypes and between different environments.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, climate change and global warming can have adverse effects on both the yield and quality of wheat. An alternative to overcome these obstacles is to use older varieties of wheat and landraces, like einkorn, emmer, and spelt, that have never been subjected to breeding practices [ 12 , 13 ].…”
Section: Productionmentioning
confidence: 99%
“…A high-fiber diet is positively associated with health benefits [ 84 , 85 ]. As well as the carbohydrate content, the ancient varieties, spelt (12%), einkorn (9.8%), and emmer (9.8%), have a lower fiber content than common wheat (13.4%) [ 13 , 65 , 86 ].…”
Section: Nutritional Value and Health Impactmentioning
confidence: 99%
See 1 more Smart Citation
“…Останніми роками, завдяки своїм дієтичним властивостям та відмінним смаковим якостям, спельта користується значним попитом серед © Корхова М. М., 2019 споживачів країн Західної Європи, Америки, Австралії, Канади [10,11].…”
Section: постановкаunclassified